2011
DOI: 10.1590/s0103-21002011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Bebê de risco: acompanhando o crescimento infantil no primeiro ano de vida

Abstract: Objective: To monitor the growth of high-risk babies in the first year of life. Methods: Analytical, cohort study, conducted with 237 babies born in Maringá -PR, between May 1 to October 31, 2008, under the Program for the Surveillance of At-Risk Infants. Results: Growth changes were present in 188 (79.3%) infants and occurred mainly after the first trimester of life. A slower than expected growth rate showed statistical association with maternal age of less than 18 years, education of less than 8 years, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
11
0
3
Order By: Relevance
“…Homogeneous distribution regarding gender was observed in the present study, corroborating the results of a previous survey (2) .…”
Section: Characterization Of At-risk Newbornssupporting
confidence: 93%
See 1 more Smart Citation
“…Homogeneous distribution regarding gender was observed in the present study, corroborating the results of a previous survey (2) .…”
Section: Characterization Of At-risk Newbornssupporting
confidence: 93%
“…Analysis of child birth and mortality conditions is necessary to guide actions of the health services, improve their quality, and guarantee early diagnosis of possible impairments that interfere in the processes of child growth and development. Actions to promote, prevent, and assist with the health of pregnant women and newborns (NB) are of fundamental importance, considering that they directly influence the health status of these individuals during childhood and into adulthood (1,2) .…”
Section: Introductionmentioning
confidence: 99%
“…(18) Low birth weight is associated with an increased perinatal mortality index and with a growth index under expectations for adolescent women and women older than 35 years. (20) The incidence of low-birth-weight newborns of women older than 30 years showed that the mean of birth weight decreased and the proportion of low-birth-weight and extremely low-birth-weight infants increased with advanced maternal age. (17) Delivery of low-birth-weight infants in advanced-age women has also been identified in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Isso tem alterado o perfil do bebê atendido, pois nem todos possuem uma síndrome ou má formação, ou encefalopatias motoras não progressivas, que refletem em atrasos nas aquisições motoras e cognitivas. Os resultados de pesquisas afirmando que a prematuridade pode provocar transtorno ao desenvolvimento, tanto motor quanto cognitivo (SASSA et al, 2011;MAGGI et al, 2014), somado ao uso de protocolos e indicadores de risco psíquico nos primeiros meses de vida do bebê (PERUZZOLO et al, 2014), coloca, em cena clínica, bebês muito novos, cujos fatores avaliados indicam descompassos nas aquisições para o seu desenvolvimento (VIEIRA; LINHARES, 2011).…”
Section: Introductionunclassified